A composite gel electrolyte and its preparation method and application
By adding basalt fiber powder to the gel electrolyte of lithium-ion batteries and using solvents and lithium salts in the electrolyte as plasticizers to form composite gel electrolytes, the safety hazards of liquid electrolytes and the complex gel electrolyte preparation process is solved. The problem of high thermal stability and low cost large-scale applications.
Patent Information
- Application Number
- CN202310457449.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-04-24
AI Technical Summary
The liquid electrolytes in existing lithium-ion batteries have safety risks, and the preparation process of most gel electrolytes is complex and has high energy consumption, making it difficult to apply on a large scale.
Compound gel electrolyte is used to form a microscopic three-dimensional structure by adding basalt fiber powder to the gel electrolyte as reinforcement filler, and using solvents and lithium salts as plasticizers in the electrolyte to form a microscopic three-dimensional structure to improve thermal stability and ionic conductivity.
It improves the thermal stability and safety of lithium-ion batteries, reduces the difficulty of battery assembly process, and greatly reduces production costs, making it suitable for large-scale applications.
Smart Images

Figure CN116487701B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite gel electrolyte and a preparation method and application thereof. Background Art
[0002] In recent years, the energy storage industry has flourished, among which electrochemical energy storage based on lithium-ion batteries has developed rapidly, and the requirements for the safety of lithium-ion batteries have been continuously improved. The electrolytes used in lithium-ion batteries are generally divided into liquid, solid and gel states. At present, the liquid electrolytes used in commercial lithium-ion batteries have great safety hazards. In recent years, there have been many safety accidents in liquid lithium-ion battery energy storage power stations, and the root cause of their combustion or explosion is the liquid electrolyte. Although all-solid-state electrolytes are highly safe, their room temperature conductivity is low, which is far from meeting the needs of practical applications. In contrast, gel electrolytes have the high ionic conductivity of liquid electrolytes and reduce free solvents, thereby reducing the risk of electrolyte leakage and the possibility of battery system combustion and explosion, greatly improving the safety of lithium-ion batteries.
[0003] However, most of the gel electrolytes are currently prepared by in-situ polymerization and coating hot pressing methods, which are complex processes, high energy consumption, and use a large amount of initiators and stabilizers, making their research still in the laboratory stage and difficult to truly apply on a large scale. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems:
[0005] CN112786961A discloses a biomass-based gel electrolyte, a lithium-ion battery, and a preparation method and application. The biomass-based gel electrolyte comprises biomass, an organic solvent and a lithium salt; the lithium-ion battery prepared by using the biomass-based gel electrolyte is not only highly safe, but also has good electrochemical properties, and the preparation method of the biomass-based gel electrolyte and the lithium-ion battery in the invention is simple and low in cost; however, the preparation process requires heating, which consumes a lot of energy, and the solubility of agar in organic solvents is poor.
[0006] CN115124641A discloses a gel electrolyte, its precursor and lithium ion battery. The interface impedance between the gel electrolyte and the pole piece is low and the conductivity is high. The gel precursor used to prepare the gel electrolyte does not require an initiator to polymerize, and can be directly dissolved in the electrolyte for cationic polymerization to form a gel electrolyte, which is simple to operate. However, the preparation process of the above-mentioned gel electrolyte requires a stabilizer, and the gel precursor needs to be heated at 40 to 50°C to polymerize to form a gel, and the polymerization reaction time is relatively long, 15 to 30 hours, which greatly increases its cost.
[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention proposes a composite gel electrolyte, in which basalt fiber powder is added as a reinforcing filler to enhance the thermal stability of the gel electrolyte and its inhibitory effect on lithium dendrites; the solvent and lithium salt in the added electrolyte can act as plasticizers to reduce the crystallinity of the gelling agent, and at the same time form a gel phase with the gelling agent to improve the ionic conductivity of the composite gel electrolyte; the gel electrolyte has a certain fluidity, and a battery can be constructed by a liquid injection method, reducing the process difficulty during battery assembly.
[0008] The composite gel electrolyte of the embodiment of the present invention includes a gelling agent, basalt fiber powder and an electrolyte.
[0009] Advantages and technical effects brought by the composite gel electrolyte of the embodiment of the present invention: 1. In the embodiment of the present invention, basalt fiber powder is added to reinforce the filler, which can form a microscopic three-dimensional structure inside the gel electrolyte, thereby enhancing the thermal stability of the gel electrolyte and its inhibitory effect on lithium dendrites; 2. In the embodiment of the present invention, an electrolyte is added, and the solvent and lithium salt in the electrolyte can be used as a plasticizer to reduce the crystallinity of the gelling agent, and at the same time form a gel phase with the gelling agent to improve the ionic conductivity of the gel electrolyte; 3. In the embodiment of the present invention, the composite gel electrolyte has good uniformity and stability, the viscosity of the system will not solidify or precipitate over time, and the fluidity is moderate, which is very suitable for application in semi-solid lithium-ion batteries and can reduce the process difficulty during battery assembly.
[0010] In some embodiments, in the composite gel electrolyte, the mass percentage of the gelling agent is 5-20%, the mass percentage of the basalt fiber powder is 15-80%, and the mass percentage of the electrolyte is 15-80%.
[0011] In some embodiments, the gelling agent comprises at least one of polyethylene oxide and polyvinyl pyrrolidone.
[0012] In some embodiments, the particle size of the basalt fiber powder is 1-100 μm.
[0013] The embodiment of the present invention further provides a method for preparing a composite gel electrolyte, comprising adding a gelling agent and basalt fiber powder into an electrolyte and stirring the mixture.
[0014] The advantages and technical effects brought by the preparation method of the composite gel electrolyte of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention does not need to use a large amount of initiator and stabilizer during the preparation process, which can greatly reduce the production cost; 2. The method of the embodiment of the present invention has a simple process and low energy consumption, which is convenient for large-scale application in industrial production.
[0015] In some embodiments, the preparation method further comprises performing ultrasonic oscillation treatment after the stirring treatment.
[0016] The embodiment of the present invention further provides a semi-solid lithium ion battery, comprising the composite gel electrolyte or the composite gel electrolyte prepared by the above method.
[0017] The advantages and technical effects brought by the semi-solid lithium-ion battery in the embodiment of the present invention are as follows: the semi-solid lithium-ion battery in the embodiment of the present invention has all the technical features of the composite gel electrolyte in the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the composite gel electrolyte in the embodiment of the present invention, which will not be repeated here.
[0018] In some embodiments, the semi-solid lithium ion battery further includes a positive electrode, a negative electrode, and a mesh porous separator.
[0019] In some embodiments, the positive electrode includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; the negative electrode includes at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metallic lithium, metallic lithium alloy, and metallic lithium composite material.
[0020] In some embodiments, the mesh porous membrane includes at least one of nylon mesh, glass fiber mesh, polyester fiber mesh, silk mesh, cotton mesh, polypropylene film, and polyethylene film. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a cycle performance diagram of a lithium-ion battery assembled using the gel electrolyte prepared in Example 1;
[0022] Figure 2 is a cycle performance diagram of a lithium-ion battery assembled using the electrolyte prepared in Comparative Example 1;
[0023] Figure 3 This is a cycle performance diagram of a lithium-ion battery using the electrolyte composition prepared in Comparative Example 3. DETAILED DESCRIPTION
[0024] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0025] The composite gel electrolyte of the embodiment of the present invention includes a gelling agent, basalt fiber powder and an electrolyte.
[0026] The composite gel electrolyte of the embodiment of the present invention adds basalt fiber powder as a reinforcing filler, which can form a microscopic three-dimensional structure inside the gel electrolyte, thereby enhancing the thermal stability of the gel electrolyte and its inhibitory effect on lithium dendrites; an electrolyte is added, and the solvent and lithium salt in the electrolyte can act as a plasticizer to reduce the crystallinity of the gelling agent, while forming a gel phase with the gelling agent to improve the ionic conductivity of the gel electrolyte; the composite gel electrolyte has good uniformity and stability, the viscosity of the system will not coagulate or precipitate over time, and the fluidity is moderate, which is very suitable for application in semi-solid lithium-ion batteries and can reduce the process difficulty during battery assembly.
[0027] In some embodiments, preferably, in the composite gel electrolyte, the mass percentage of the gelling agent is 5-20%, the mass percentage of the basalt fiber powder is 15-80%, and the mass percentage of the electrolyte is 15-80%. Further preferably, in the composite gel electrolyte, the mass percentage of the gelling agent is 10-15%, the mass percentage of the basalt fiber powder is 30-50%, and the mass percentage of the electrolyte is 40-60%.
[0028] In the embodiment of the present invention, the dosage of the gelling agent, basalt fiber powder and electrolyte is preferably selected. By using the gelling agent addition amount within the ratio range, the uniformity and stability of the gel electrolyte are better, and the fluidity is moderate. If the gelling agent content ratio is too low, it can only increase the viscosity of the electrolyte, but the electrolyte cannot form a gel. If the gelling agent content ratio is too high, the formed electrolyte has poor fluidity and cannot be mixed evenly. After adding the reinforcing filler, the filler is easy to agglomerate. By using the basalt fiber powder within the ratio range, it can form a three-dimensional structure in the gel electrolyte, enhance the inhibition of the composite gel electrolyte on lithium dendrites, and has the effect of enhancing the thermal stability of the electrolyte and preventing thermal runaway of the semi-solid lithium ion battery. It has a good effect. If the basalt fiber powder content ratio is too low, the improvement of electrolyte performance is limited; if the basalt fiber powder content ratio is too high, the possibility of basalt fiber powder agglomeration will increase, resulting in reduced electrolyte uniformity and stability; the solvent and lithium salt in the electrolyte can be used as plasticizers to reduce the crystallinity of the gelling agent, and at the same time form a gel phase with the gelling agent, so that the ionic conductivity of the gel electrolyte is improved. If the electrolyte content ratio is too low, the ionic conductivity of the composite gel electrolyte is reduced, thereby reducing the cycle and rate performance of the lithium-ion battery using the composite gel electrolyte. If the electrolyte content ratio is too high, it will increase costs and increase the risk of electrolyte leakage and battery thermal runaway.
[0029] In some embodiments, preferably, the gelling agent comprises at least one of polyethylene oxide and polyvinyl pyrrolidone (PVP). Further preferably, the gelling agent is polyethylene oxide.
[0030] In the embodiment of the present invention, the type of gelling agent is preferably selected. Compared with other gelling agents, polyethylene oxide has low cost, excellent performance, and strong liquid retention ability, which can prevent safety problems caused by electrolyte leakage that may occur during battery operation; polyvinyl pyrrolidone is used as a gelling agent, which has good film-forming, adhesion, hygroscopicity and liquid retention, low toxicity, can be dissolved in most organic solvents, and can improve the cycle performance of positive and negative electrodes to a certain extent.
[0031] In some embodiments, preferably, the particle size of the basalt fiber powder is 1-100 μm. Further preferably, the particle size of the basalt fiber powder is 50 μm.
[0032] In the embodiment of the present invention, the size of the basalt fiber powder is preferably selected, which can form a relatively complete three-dimensional network structure inside the electrolyte and further improve the strength of the electrolyte. If the size of the basalt fiber powder is too small, it is not conducive to the formation of a three-dimensional network structure inside the electrolyte, and the improvement of the strength of the electrolyte is limited; if the size of the basalt fiber powder is too large, it is not conducive to the uniform distribution of the basalt fiber powder in the electrolyte system, and it is not conducive to the formation of a gel electrolyte with good fluidity.
[0033] The embodiment of the present invention further provides a method for preparing a composite gel electrolyte, comprising adding a gelling agent and basalt fiber powder into an electrolyte and stirring the mixture.
[0034] The preparation method of the composite gel electrolyte of the embodiment of the present invention does not need to use a large amount of initiator and stabilizer during the preparation process, which can greatly reduce the production cost; the process is simple and the energy consumption is low, which is convenient for large-scale application in industrial production.
[0035] In some embodiments, preferably, the preparation method further comprises performing ultrasonic oscillation treatment after the stirring treatment.
[0036] In the embodiment of the present invention, ultrasonic oscillation treatment is performed after stirring to remove bubbles therein and ensure the quality of the gel electrolyte.
[0037] In some embodiments, preferably, the stirring treatment time is 1 to 10 hours. More preferably, the stirring treatment time is 3 to 7 hours.
[0038] The embodiment of the present invention further provides a semi-solid lithium ion battery, comprising the composite gel electrolyte or the composite gel electrolyte prepared by the above method.
[0039] The semi-solid lithium-ion battery of the embodiment of the present invention has all the technical features of the composite gel electrolyte of the embodiment of the present invention, and therefore has all the advantages and technical effects brought by the composite gel electrolyte of the embodiment of the present invention, which will not be described in detail here.
[0040] In some embodiments, preferably, a positive electrode, a negative electrode and a mesh porous separator are also included. Further preferably, the positive electrode includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; the negative electrode includes at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metal lithium, metal lithium alloy, and metal lithium composite material.
[0041] In some embodiments, preferably, the mesh porous membrane comprises at least one of nylon mesh, glass fiber mesh, polyester fiber mesh, silk mesh, cotton mesh, polypropylene film, and polyethylene film.
[0042] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.
[0043] Example 1
[0044] (1) 10 parts by weight of PEO and 40 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 50 parts by weight of electrolyte, and stirred for 5 hours;
[0045] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain a composite gel electrolyte with a certain flow state.
[0046] In the composite gel electrolyte prepared in this embodiment, the mass percentage of PEO is 10%, the mass percentage of basalt fiber is 40%, and the mass percentage of electrolyte is 50%.
[0047] Example 2
[0048] (1) 10 parts by weight of PEO and 30 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 60 parts by weight of electrolyte, and stirred for 5 hours;
[0049] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain a composite gel electrolyte with a certain flow state.
[0050] In the composite gel electrolyte prepared in this embodiment, the mass percentage of PEO is 10%, the mass percentage of basalt fiber is 30%, and the mass percentage of electrolyte is 60%.
[0051] Example 3
[0052] (1) 10 parts by weight of PEO and 50 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 40 parts by weight of electrolyte, and stirred for 5 hours;
[0053] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain a composite gel electrolyte with a certain flow state.
[0054] In the composite gel electrolyte prepared in this embodiment, the mass percentage of PEO is 10%, the mass percentage of basalt fiber is 50%, and the mass percentage of electrolyte is 40%.
[0055] Example 4
[0056] (1) 10 parts by weight of PVP and 40 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 50 parts by weight of electrolyte, and stirred for 5 hours;
[0057] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain a composite gel electrolyte with a certain flow state.
[0058] In the composite gel electrolyte prepared in this embodiment, the mass percentage of PVP is 10%, the mass percentage of basalt fiber is 40%, and the mass percentage of electrolyte is 50%.
[0059] Comparative Example 1
[0060] (1) 1 part by weight of PEO and 9 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 90 parts by weight of electrolyte, and stirred for 5 hours;
[0061] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain an electrolyte.
[0062] In the electrolyte prepared in this comparative example, the mass percentage of PEO is 1%, the mass percentage of basalt fiber is 9%, and the mass percentage of electrolyte is 90%.
[0063] Comparative Example 2
[0064] (1) 1 part by weight of PEO and 90 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added to 9 parts by weight of electrolyte, and stirred for 5 hours;
[0065] (2) Ultrasonic oscillation treatment is performed to remove bubbles and obtain an electrolyte.
[0066] In the electrolyte prepared in this comparative example, the mass percentage of PEO is 1%, the mass percentage of basalt fiber is 90%, and the mass percentage of electrolyte is 9%.
[0067] Comparative Example 3
[0068] 10 parts by weight of PEO and 40 parts by weight of basalt fiber powder with a particle size of 50 μm were mixed and added into 50 parts by weight of electrolyte, and stirred for 0.5 h to obtain a composite gel electrolyte.
[0069] In the composite gel electrolyte prepared in this comparative example, the mass percentage of PEO is 10%, the mass percentage of basalt fiber is 40%, and the mass percentage of electrolyte is 50%.
[0070] Comparative Example 4
[0071] The preparation method of this comparative example is the same as that of Example 1, except that in step (1), the basalt fiber powder is replaced by nano-silicon dioxide.
[0072] Comparative Example 5
[0073] The preparation method of this comparative example is the same as that of Example 1, except that in step (1), the basalt fiber powder is replaced by cellulose acetate.
[0074] The performance of the composite gel electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested, and the results are shown in Table 1. The prepared electrolytes were assembled into a semi-solid lithium-ion battery with a nylon mesh, a lithium iron phosphate positive electrode and a graphite negative electrode, and the cycle performance of the lithium-ion battery was tested, and the results are shown in Table 1.
[0075] The electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 3 were assembled into corresponding batteries and cycled at current densities of 0.1C, 0.5C, 1C and 0.5C, respectively; the results are as follows: Figure 1 , Figure 2 and Figure 3 shown.
[0076] Table 1
[0077]
[0078]
[0079] Note: Excellent means that the charge and discharge cycle is stable and has no fluctuation; Good means that the charge and discharge cycle is relatively stable without obvious fluctuation; Poor means that the charge and discharge cycle is unstable with obvious fluctuation; ◎ means that it has good inhibition on lithium dendrites; the weight loss in a 60℃ oven for 1h is less than 10%, and the thermal stability is good; the electrolyte leveling time is <10min after the container containing the electrolyte is tilted 45°, and the fluidity is good; ○ means that it has a certain inhibitory effect on lithium dendrites; the weight loss in a 60℃ oven for 1h is about 10~30%, and the thermal stability is general; the electrolyte leveling time is 10min~2h after the container containing the electrolyte is tilted 45°, and the fluidity is general; × means that there is no inhibitory effect on lithium dendrites; the weight loss in a 60℃ oven for 1h is greater than 30%, and the thermal stability is poor; the formulated material cannot form a fluid gel electrolyte or the electrolyte leveling time is >2h after the container containing the electrolyte is tilted 45°, and the fluidity is poor.
[0080] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0081] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A composite gel electrolyte, characterized in that: It includes gelling agent, basalt fiber powder and electrolyte; In the composite gel electrolyte, the mass percentage of the gelling agent is 5-20%, the mass percentage of the basalt fiber powder is 15-80%, and the mass percentage of the electrolyte is 15-80%; The gelling agent is at least one of polyethylene oxide and polyvinyl pyrrolidone; The preparation method of the composite gel electrolyte comprises adding a gelling agent and basalt fiber powder into an electrolyte, and performing a stirring treatment; and performing an ultrasonic oscillation treatment after the stirring treatment.
2. The composite gel electrolyte according to claim 1, characterized in that: The particle size of the basalt fiber powder is 1-100 μm.
3. A semi-solid lithium-ion battery, characterized in that: The invention comprises the composite gel electrolyte according to any one of claims 1 to 2.
4. The semi-solid lithium ion battery according to claim 3, characterized in that: It also includes a positive electrode, a negative electrode and a mesh porous separator.
5. The semi-solid lithium ion battery according to claim 4, characterized in that: The positive electrode includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; the negative electrode includes at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metallic lithium, metallic lithium alloy, and metallic lithium composite material.
6. The semi-solid lithium ion battery according to claim 4 or 5, characterized in that: The mesh porous diaphragm includes at least one of nylon mesh, glass fiber mesh, polyester fiber mesh, silk mesh, cotton mesh, polypropylene film, and polyethylene film.
Citation Information
Patent Citations
Biomass-based gel electrolyte, lithium ion battery, preparation method and application
CN112786961A
Gel electrolyte, precursor thereof and lithium ion battery
CN115124641A
Membrane for flexible solid super capacitor and preparation method thereof
CN102360950A
Polymer membrane, preparation method thereof, electrolyte possessing polymer membrane and cell
CN104177738A